2022
DOI: 10.1002/jor.25273
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the extracellular signal‐regulated kinase pathway reduces the inflammatory component in nucleus pulposus cells

Abstract: Intervertebral disc (IVD) degeneration is a spinal disorder that triggers an inflammatory response and subsequent development of spinal pseudoarthrosis. The aim of the present study is to elucidate the role of the extracellular signal‐regulated kinase (ERK) pathway in inflammation‐induced IVD cells. Inflammatory human nucleus pulposus (NP) cells (NPCs) were induced using tumor necrosis factor‐α and the ERK pathway was blocked using a selective molecule‐based inhibitor U0126. Gene expression of catabolic and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In contrast, IVD studies indicate that the ERK/MAPK signaling pathway is activated by excessive ROS in IVD cells and promotes IVD degeneration, including extracellular matrix reduction, apoptosis, and cell damage [ 36 , 38 , 39 ]. Thus, the inhibition of ERK signaling is considered a potential treatment for IVD degeneration as it provides some protection against the adverse effects of TNF-α in the IVD [ 43 ]. Meanwhile, hypoxia-induced ERK phosphorylation and ERK activation was shown to be necessary for NP cell survival under hypoxic conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IVD studies indicate that the ERK/MAPK signaling pathway is activated by excessive ROS in IVD cells and promotes IVD degeneration, including extracellular matrix reduction, apoptosis, and cell damage [ 36 , 38 , 39 ]. Thus, the inhibition of ERK signaling is considered a potential treatment for IVD degeneration as it provides some protection against the adverse effects of TNF-α in the IVD [ 43 ]. Meanwhile, hypoxia-induced ERK phosphorylation and ERK activation was shown to be necessary for NP cell survival under hypoxic conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that disc degeneration could produce a large number of inflammatory factors, such as TNF- α and IL-1 β [ 20 ]. As an initiation factor of inflammation, TNF- α can stimulate the expression of other inflammatory factors, and there is also a synergy between TNF- α and the stimulated inflammatory factors, such as IL-1 β , showing a “positive feedback” effect [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CCK-8 results showed that after being treated with 500 μg/ml LPS, the integrated optical density (IOD) values decreased significantly (P < 0:01) (Figure 2(a)); we therefore established the apoptosis model by treating NPCs with 500 μg/ml LPS. After being treated with BMSC-Exo gradient concentration (12,16,20, and 30 μg/ml) for 48 h, the viability of NPCs increased gradually (Figure 2(b)). Compared with the control group, the mRNA expression of COL2A1 significantly decreased, while the expression of Beclin-1 and IL-1β significantly increased in the model group (treated with 500 μg/ml LPS) (P < 0:01); compared with the model group, the mRNA expression of COL2A1 and Beclin-1 increased significantly, while the expression of IL-1β decreased in the exosome treatment group (treated with 500 μg/ml LPS and 20 μg/ml BMSC-Exo) (P < 0:01); compared with the exosome treatment group, the mRNA expression of COL2A1 and Beclin-1 decreased significantly, while the expression of IL-1β increased significantly in the autophagy inhibition group (treated with 500 μg/ml LPS, 20 μg/ml BMSC-Exo, and 10 mM 3-MA) (P < 0:01) (Figure 2(c)).…”
Section: Bmsc-exo Inhibits Npc Apoptosis By Promotingmentioning
confidence: 99%
“…The present results indicate that the signature study of nucleus pulposus cells and inflammatory responses in disc degeneration and degenerative disc disease has a larger total frequency of induction. In the research field of intervertebral disc degeneration, nucleus pulposus cells and inflammatory response are frequently cited keywords in this field [27].…”
Section: Acknowledgementmentioning
confidence: 99%